Respuesta :
The function results [tex]f(x) = -3(x - 1)5 + 2[/tex] after applying a sequence of transformations [tex]f(x) = x^5[/tex].
We have to determine, which function results after applying the sequence of transformations [tex]f(x) = x^5[/tex].
According to the question,
To find the sequence of the transformation of the given function following all the steps given below.
Function; [tex]f(x) = x^5[/tex]
- Step1; Stretch vertically by 3 in the negative x-axis.
[tex]f(x) = -3[(x )^5][/tex]
- Step2; Reflect the function across the x-axis,
[tex]f(x) = -3(x)^5[/tex]
- Step3; Shifting the function 1 unit right,
[tex]f(x) = -3(x-1)^5[/tex]
- Step4; Shifting the function upward 2 units,
[tex]f(x) = -3(x-1)^5 +2[/tex]
Hence, The function results [tex]f(x) = -3(x - 1)5 + 2[/tex] after applying a sequence of transformations [tex]f(x) = x^5[/tex].
To know more about Function click the link given below.
https://brainly.com/question/14418346